ROAD DAMAGE EVALUATION ON RIGID PAVEMENT WITH PAVEMENT CONDITION INDEX METHOD IN KLAKAH REJO-BENOWO ROAD, SURABAYA CITY, EAST JAVA - Mestuni, Welsi Buy; Hartatik, Nurani (Fakultas Teknik Universitas Tanjungpura, 2023)
The research objective was to analyze the level and type of damage from every kind of damage on the Klakah Rejo Benowo road by calculating the rigid pavement condition index value and providing solutions. This study took the location of the Klakah Rejo-Benowo road section, Surabaya City